Three-Dimensional Distribution of Transverse Collagen Fibers in the Anterior Human Corneal Stroma - Winkler, Moritz (Invest Ophthalmol Vis Sci, 2013)
PURPOSE. Recent investigations of human corneal structure and biomechanics have shown that stromal collagen fibers (lamellae) are organized into a complex, highly intertwined three-dimensional meshwork of transverse oriented fibers that increases stromal stiffness and controls corneal shape. The purpose of this study was to characterize the three-dimensional distribution of transverse collagen fibers along the major meridians of the cornea using an automated method to rapidly quantify the collagen fibers' angular orientation. METHODS. Three eyes from three donors were perfusion-fixed under pressure, excised, and cut into four quadrants. Quadrants were physically sectioned using a vibratome and scanned using nonlinear optical high-resolution macroscopy. Planes were analyzed numerically using software to identify collagen fiber angles relative to the corneal surface, stromal depth, and radial position within the anterior 250 μm of the stroma. RESULTS. The range of fiber angles and the fiber percentage having an angular displacement greater than ±3.5° relative to the corneal surface (“transverse fibers”) was highest in the anterior stroma and decreased with depth. Numerical analysis showed no significant differences in fiber angles and transverse fibers between quadrants, meridians, and radial position. CONCLUSIONS. These results match our previous observation of a depth-dependent gradient in stromal collagen interconnectivity in the central cornea, and show that this gradient extends from the central cornea to the limbus. The lack of a preferred distribution of angled fibers with regard to corneal quadrant or radial position likely serves to evenly distribute loads and to avoid the formation of areas of stress concentration.